The Global Solution and Asymptotic Behaviors for One Class of System of Nonlinear Evolution Equations (Journal of Partial Differential Equations, 1997)
The existence of global solution of initial-value problem for one class of system of nonlinear evolution equation is proved, we also study the asymptotic behavior and “blow up” of the solution.
Keywords: Global solutions; evolution equations; asymptotic behaviors